The current state of road constructionproduction in Zhambyl region - Shaushenova, S.G.; Niyazbekova, Sh.U.; Nurpeisova А.А.; Yerzhanova, S.K. (BUKETOV BUSINESS REVIEW, 2019)
The article discusses the issues of economic efficiency of road construction modernization, assesses the development of the current state of road construction production and addresses the problems of economic efficiency of road construction production in the Zhambyl region. Since road construction, the purpose of which is to create the country’s transport system, including the road network, has been and remains one of the main production areas, providing solutions to both national and regional socio-economic problems, since the state and development of roads directly affects gross product, price level, coefficient of commercial use of roads by industries.The transport potential of the region is not only the object of management, but also determines the possibilities of socio-economic development of the region. It is concluded that the transport industry should develop at a faster pace than other sectors of the economy.In a market economy and high growth of the country’s automobilization, restructuring and modernization of the road construction industry is needed, using innovative mechanisms for financing and rational use of funds in the road construction industry.